DETERMINAN MATRIKS ORDO 3X3 DENGAN METODE MINOR DAN KOFAKTOR - Sri Yulianti; Risman Bustaman (Jurnal Pustaka Cendekia Pendidikan, 2025)
Minor and cofactor methods are general methods that can be used to determine the determinant of matrices. Calculation of the determinant of the matrix with the minor and cofactor methods can be applied to all sizes of square matrices. The determinant of the matrix can be calculated from the minor and the cofactor in one of the rows or columns of the matrix. Before determining the cofactor, we must first determine the submatrix or minor. Definition 2.3 The minor of a matrix A denoted by M_ij is a matrix of parts of A which is obtained by removing the elements in the ith row and the elements in the jth column. Definition 2.4 The cofactor of an element of the I-th row and j-column of matrix A is denoted by K_ij=〖(-1)〗^(i+j) M_ij. To determine the determinant of a matrix using the minor and cofactor method, it is sufficient to take only one expansion.